Saving dynamics in the Asian countries - Baharumshah, Ahmad Zubaidi; Thanoon, Marwan A.; Rashid, Salim (Elsevier, 2003)
This paper investigates empirically the factors that have influenced the savings behavior in the fast growing Asian economies-Singapore, South Korea, Malaysia, Thailand and the Philippines. Both the short and long-run movements of savings are modeled during the 1960-1997. The empirical results of the analysis based on time series data may be summarized as follows: (i) foreign savings deters domestic saving both in the short and long run; (ii) savings does not Granger cause economic growth, except for Singapore; (iii) the effect of interest rate on saving in Asian countries is inconclusive and it reflects the extent of financial liberalization adopted in these countries; and (iv) in the long run the causality runs from foreign to domestic savings.